Electrospun Orodispersible Films of Isoniazid for Pediatric Tuberculosis Treatment - Konstantina Chachlioutaki; Emmanouil K. Tzimtzimis; Dimitrios Tzetzis; Ming-Wei Chang; Zeeshan Ahmad; Christina Karavasili; Dimitrios G. Fatouros (MDPI AG, 2020)
Child-appropriate dosage forms are critical in promoting adherence and effective pharmacotherapy in pediatric patients, especially those undergoing long-term treatment in low-resource settings. The present study aimed to develop orodispersible films (ODFs) for isoniazid administration to children exposed to tuberculosis. The ODFs were produced from the aqueous solutions of natural and semi-synthetic polymer blends using electrospinning. The spinning solutions and the resulting fibers were physicochemically characterized, and the disintegration time and isoniazid release from the ODFs were assessed in simulated salivary fluid. The ODFs comprised of nanofibers with adequate thermal stability and possible drug amorphization. Film disintegration occurred instantly upon contact with simulated salivary fluid within less than 15 s, and isoniazid release from the ODFs in the same medium followed after the disintegration profiles, achieving rapid and total drug release within less than 60 s. The ease of administration and favorable drug loading and release properties of the ODFs may provide a dosage form able to facilitate proper adherence to treatment within the pediatric patient population.